Psychometric evaluation of a motor control test battery of the craniofacial region. (30th September 2017) - von Piekartz, H.; Stotz, E.; Both, A.; Bahn, G.; Armijo‐Olivo, S.; Ballenberger, N.
Summary: The primary objective of this study was to determine the structural and known‐group validity as well as the inter‐rater reliability of a test battery to evaluate the motor control of the craniofacial region. Seventy volunteers without TMD and 25 subjects with TMD (Axes I) per the DC/TMD were asked to execute a test battery consisting of eight tests. The tests were video‐taped in the same sequence in a standardised manner. Two experienced physical therapists participated in this study as blinded assessors. We used exploratory factor analysis to identify the underlying component structure of the eight tests. Internal consistency (Cronbach's α), inter‐rater reliability (intra‐class correlation coefficient) and construct validity (ie, hypothesis testing‐known‐group validity) (receiver operating curves) were also explored for the test battery. The structural validity showed the presence of one factor underlying the construct of the test battery. The internal consistency was excellent (0.90) as well as the inter‐rater reliability. All values of reliability were close to 0.9 or above indicating very high inter‐rater reliability. The area under the curve (AUC) was 0.93 for rater 1 and 0.94 for rater two, respectively, indicating excellent discrimination between subjects with TMD and healthy controls. The results of the present study support the psychometric properties of test battery to measure motor control of the craniofacial region when evaluated through videotaping. This test battery could be used to differentiate between healthy subjects and subjects with musculoskeletal impairments in the cervical and oro‐facial regions. In addition, this test battery could be used to assess the effectiveness of management strategies in the craniofacial region.